Microstructure and property modification of cold sprayed coatings using different grain sizes of Cr3C2-25 (Ni20Cr) composite powder - Trelka, Anna (Strojniški vestnik, 2020)
This article describes the microstructure and mechanical properties of Cr3C2-25(Ni20Cr) cermet coatings cold-sprayed on Al 7075 alloy substrates. The study aimed to determine the effect of three different powder grain sizes and three different standoff distances on the microstructure (phase composition, surface topography, volume fraction and distribution of the Cr3C2 phase in the Ni20Cr matrix and porosity) and the mechanical properties (hardness and abrasive wear resistance) of the Cr3C2-25(Ni20Cr) coatings. The examinations revealed that the thickness of the coatings obtained with the same duration and feed rate decreased with increasing powder grain size and standoff distance. The coatings produced from powders with smaller particles had higher hardness and more compact structures than the coatings obtained from powders where the particles were larger (more than 40 %m). The coatings produced from finer powders were also more resistant to abrasive wear.
Keywords: cold spraying; Cr3C2-25(Ni20Cr) composite coating; kompozitna prevleka Cr3C2-25(Ni20Cr); mechanical properties; mehanske lastnosti; microstructure; mikrostruktura; nabrizgavanje v hladnem; odmik; powder grain size; standoff distance; velikost zrn prahu